Availability-aware mapping of service function chains - Jingyuan Fan; Chaowen Guan; Yangming Zhao; Chunming Qiao (IEEE INFOCOM 2017 - IEEE Conference on Computer Communications, 2017)
Network Function Virtualization (NFV) is a promising technique to greatly improve the effectiveness and flexibility of network services through a process named Service Function Chain (SFC) mapping, with which different network services are deployed over virtualized and shared platforms in data centers. However, such an evolution towards software-defined network functions introduces new challenges to network services which require high availability. One effective way of protecting the network services is to use sufficient redundancy. By doing so, however, the efficiency of physical resources may be greatly decreased. To address such an issue, this paper defines an optimal availability-aware SFC mapping problem and presents a novel online algorithm that can minimize the physical resources consumption while guaranteeing the required high availability within a polynomial time. Simulation results show that our proposed algorithm can significantly improve SFC mapping request acceptance ratio and reduce resource consumption.